Cutaneous Side Effects of BRAF Inhibitors in Advanced Melanoma: Review of the Literature - Bilgen Gençler; Müzeyyen Gönül (Hindawi Limited, 2016)
The incidence of melanoma has recently been increasing. BRAF mutations have been found in 40-60% of melanomas. The increased activity of BRAF V600E leads to the activation of downstream signaling through the mitogen-activated protein kinase (MAPK) pathway, which plays a key role as a regulator of cell growth, differentiation, and survival. The use of BRAF inhibitors in metastatic melanoma with BRAF mutation ensures clinical improvement of the disease. Vemurafenib and dabrafenib are two selective BRAF inhibitors approved by the Food and Drug Administration (FDA). Both drugs are well tolerated and successfully used in clinical practice. However, some adverse reactions have been reported in patients in the course of treatment. Cutaneous side effects are the most common adverse events among them with a broad spectrum. Both the case reports and several original clinical trials reported cutaneous reactions during the treatment with BRAF inhibitors. In this review, the common cutaneous side effects of BRAF inhibitors in the treatment of metastatic melanoma with BRAF V600E mutation were reviewed.